STRIPE3, encoding a human dNTPase SAMHD1 homolog, regulates chloroplast development in rice. (October 2022) - Wang, Hong; Tu, Ranran; Ruan, Zheyan; Wu, Duo; Peng, Zequn; Zhou, Xingpeng; Liu, Qunen; Wu, Weixun; Cao, Liyong; Cheng, Shihua; Sun, Lianping; Zhan, Xiaodeng; et al.
Abstract: Chloroplast is an important organelle for photosynthesis and numerous essential metabolic processes, thus ensuring plant fitness or survival. Although many genes involved in chloroplast development have been identified, mechanisms underlying such development are not fully understood. Here, we isolated and characterized the stripe3 ( st3 ) mutant which exhibited white-striped leaves with reduced chlorophyll content and abnormal chloroplast development during the seedling stage, but gradually produced nearly normal green leaves as it developed. Map-based cloning and transgenic tests demonstrated that a splicing mutation in ST3, encoding a human deoxynucleoside triphosphate triphosphohydrolase (dNTPase) SAMHD1 homolog, was responsible for st3 phenotypes. ST3 is highly expressed in the third leaf at three-leaf stage and expressed constitutively in root, stem, leaf, sheath, and panicle, and the encoded protein, OsSAMHD1, is localized to the cytoplasm. The st3 mutant showed more severe albino leaf phenotype under exogenous 1-mM dATP/dA, dCTP/dC, and dGTP/dG treatments compared with the control conditions, indicating that ST3 is involved in dNTP metabolism. This study reveals a gene associated with dNTP catabolism, and propose a model in which chloroplast development in rice is regulated by the dNTP pool, providing a potential application of these results to hybrid rice breeding. Highlights: A splicing mutation in ST3 / OsSAMHD1 leads to white-striped leaves. ST3 is required for chloroplast development during the seedling stage. st3 phenotypes are affected by low temperatures during maturation. ST3 is constitutively expressed and its encoded protein is localized to cytoplasm. ST3 is involved in dNTP metabolism to regulate rice chloroplast development.